Bahasa Inggris - Persis, Jennifer; Hadi, Ido Prijana; Yogatama , Astri (LPPM Stikosa - AWS, 2025)
The role of a brand ambassador is considered strategic, as it helps build an emotional connection between a brand and its consumers. The use of Korean celebrities as brand ambassadors has become common among Indonesian products due to the global popularity of Korean culture, known as the “Korean Wave.” This study aims to measure the effectiveness of NCT Dream as the brand ambassador of the TosTos snack product among non-Gen Z audiences using the VisCAP model, which includes four components: Visibility, Credibility, Attraction, and Power. This model is considered effective in evaluating how well a brand ambassador conveys a brand message. The research used a descriptive quantitative method, with data collected through an online questionnaire. The sampling technique was non-probability quota sampling, involving 400 respondents from the general public aged 28 years and older who are familiar with NCT Dream as TosTos’s brand ambassador. The findings indicate that NCT Dream is effective as a brand ambassador for TosTos, even among millennial and older age groups, with the “Visibility” component receiving the highest score among the four indicators.